2019
DOI: 10.5435/jaaosglobal-d-19-00143
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study Comparing a Patient-specific Design Total Knee Arthroplasty With an Off-the-Shelf Design: Unexpected Catastrophic Failure Seen in the Early Patient-specific Design

Abstract: Background:Patient-specific design (PSD) total knee arthroplasty implants are marketed to restore neutral mechanical-axis alignment (MAA) and provide better anatomic fit compared with standard off-the-shelf (OTS) total knee arthroplasty designs. The purpose was to compare the Knee Society scores, radiographic outcomes, and complications of PSD and OTS implants.Methods:Retrospective study analyzing PSD and OTS by a single surgeon. Implant design change in PSD occurred during the period of data collection leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…In contrast, Schwarzkopf et al [ 24 ] reported a decrease of 3.44° (range, −83° to 55°) in ROM after TKA with PSI, whereas patients receiving OTS implants showed an increase of 1.54° (range, −80° to 90°, p < 0.1). The remaining authors did not observe statistically significant differences in ROM between both groups [ 20 , 22 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In contrast, Schwarzkopf et al [ 24 ] reported a decrease of 3.44° (range, −83° to 55°) in ROM after TKA with PSI, whereas patients receiving OTS implants showed an increase of 1.54° (range, −80° to 90°, p < 0.1). The remaining authors did not observe statistically significant differences in ROM between both groups [ 20 , 22 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 98%
“…The literature search yielded a total of 1430 publications and, after allocation processes shown in Figure 1 , 13 articles met the criteria for this systematic review. Of these articles, 11 investigated the outcomes after TKA [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and two investigated the outcomes after UKA [ 27 , 28 ] with PSI versus OTS implants. There were four prospective cohort studies and nine retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, spinal surgeons and pioneers must not allow a sound theoretical basis, successful application in other fields and encouraging early results to drive unsubstantiated, widespread application, as some argue has occurred with certain Minimally Invasive Spinal Surgeries (MISS) [42]. Further, the possibility of unforeseen implant-related complications must not be discounted, either due to issues in the planning and implementation of a PSI [6] or inherent to the implant design or material [11,18,43].…”
Section: Discussionmentioning
confidence: 99%